Analyses of meteorology information during Malaysian flood disaster 2014 - Basri, Atikah Balqis; Ismail, Ahmad Fadzil; Badron, Khairayu; Khairolanuar, Muhamad Haziq; Mohd Sobli, Nuurul Hudaa (American Scientific Publishers, 2016)
In this paper, we analyze the rain gauge data and radar data in the duration of time, T over the area covered by meteorological radar and rain gauge. T can be the whole duration for the rain event before, during and after the flood tragedy. The procedure is applied to a set of data composed of Constant Altitude Plan Position (CAPPI) scans for the absolute size of cloud from weather radar and rainfall measurement provided by rain gauge data. The procedure was applied to 14 days precipitation phenomenon observed in Kota Bharu, Kelantan (Malaysia) from 13 December 2014 until 26 December 2014. The objective of the research is to derive the tropical flood estimation model.